2018
DOI: 10.1371/journal.pone.0202521
|View full text |Cite
|
Sign up to set email alerts
|

Mate Yako Afya Yako: Formative research to develop the Tanzania HIV self-testing education and promotion (Tanzania STEP) project for men

Abstract: The purpose of this formative research, guided by the Integrated Behavioral Model, was to assess men’s attitudes and personal agency towards HIV self-testing (HIVST) and confirmatory HIV testing in order to inform the development of the Tanzania STEP (Self-Testing Education and Promotion) Project, a peer-based HIV self-testing intervention for young men in Tanzania. Qualitative in-depth interviews were conducted with 23 men in Dar es Salaam, Tanzania who socialize in networks locally referred to as “camps”. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(89 citation statements)
references
References 55 publications
(70 reference statements)
1
87
0
Order By: Relevance
“…Positive attitudes towards HIVST were primarily related to enjoying the freedom to test for HIV in the privacy and at a convenient place of their choice, and relief to avoid needle pricks for using the oral-fluid sample, which is a less invasive and painless procedure. These findings are in line with studies done in other settings [44][45][46]. Thus, we expect that future HIVST intervention using oral-fluid samples among FBWs and MCPs is more likely to be accepted in Northern Tanzania.…”
Section: Attitudes About Hivstsupporting
confidence: 90%
See 1 more Smart Citation
“…Positive attitudes towards HIVST were primarily related to enjoying the freedom to test for HIV in the privacy and at a convenient place of their choice, and relief to avoid needle pricks for using the oral-fluid sample, which is a less invasive and painless procedure. These findings are in line with studies done in other settings [44][45][46]. Thus, we expect that future HIVST intervention using oral-fluid samples among FBWs and MCPs is more likely to be accepted in Northern Tanzania.…”
Section: Attitudes About Hivstsupporting
confidence: 90%
“…Our results showed mixed findings on the participant's confidence in their capacity to use the HIVST. Interestingly, men compared to women, reported high confidence in using HIVST correctly after face-to-face counseling with a trained counselor, parallel to findings from a study conducted in Tanzania [46]. However, female participants expressed a lack of confidence in using HIVST in privacy, underscoring the importance of self-efficacy influence on an individual's confidence in their ability to perform a new technology [56,71].…”
Section: Self-efficacy Towards Hivstmentioning
confidence: 72%
“…Several studies have called for the need for the implementation of policies that advocate for men's health [49][50][51]. Tailored HEPs to improve men's uptake of HTSs have been recommended [52]. As HIVST is relatively new in Rwanda [11], there is need for the implementation of guidelines and policies that advocate for men's engagement in this new intervention and for the scaling up thereof [53].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that males in low-to middle-income countries (LMICs) are not accessing health services as much as their female counterparts resulting in worse outcomes which include mortality [1,2,8]. Health education programs (HEPs) have been recommended to address poor health seeking behavior among key populations including men [9,10]. HEPs are a form of health promotion through health literacy and are immensely beneficial in keeping people alive by providing valued services to populations, information on combating various diseases and promoting health awareness [11].…”
Section: Introductionmentioning
confidence: 99%
“…Ensuring healthy lives and promoting well-being for all at all ages is one of the key agendas adopted by the UN General Assembly for 2030 [12]. Gender-specific strategies for care delivery, health education, and research are key to achieving these goals, particularly in disease-burdened LMICs [9,[13][14][15]. A 2007 World Health Organization (WHO) review of interventions designed to involve men and boys in achieving gender equality and better health concluded that well-designed male involvement interventions would be more effective at improving men's attitudes and behaviors toward sexual and reproductive health and other health conditions [16].…”
Section: Introductionmentioning
confidence: 99%